Effect of Individual Characteristics on Perception of Usability and Perception of Ease in Use of Mobile Commerce - Rahajeng, Lila; Kaluge, David (Politeknik Negeri Madiun, 2019)
This research study discusses the differences in individual characteristics associated through the use of mobile commerce with the perception of usefulness (Usefulness) and perceptions of convenience (Easy to Use) by converting the Technology Acceptance Model (TAM) model developed by Davis in 1989. The research was conducted at the Faculty of Economics and Business Universitas Brawijaya Malang using the survey method. The researcher received a response of 35 accounting students who used mobile commerce services. The researcher used the SPSS Software application to study the research data. This study uses the Multivariate Analysis of Variance (MANOVA) test. The results of the analysis for this model reveal the use of mobile commerce services there are individual level differences in the use of m-commerce (perceptions of usability and perceived ease) in each individual category of respondents' characteristics (Age, Gender, Innovation). The implications of this study are relevant to management and system analysis for benefit factors and consider the use of use in using and developing mobile commerce transactions.